F-Measure Optimisation and Label Regularisation for Energy-Based Neural Dialogue State Tracking Models - Kelleher, John (My University, 2020)
In recent years many multi-label classification methods have exploited label dependencies to improve performance of classification tasks in various domains, hence casting the tasks to structured prediction problems. We argue that multi-label predictions do not always satisfy domain constraint restrictions. For example when the dialogue state tracking task in task-oriented dialogue domains is solved with multi-label classification approaches, slot-value constraint rules should be enforced following real conversation scenarios. To address these issues we propose an energy-based neural model to solve the dialogue state tracking task as a structured prediction problem. Furthermore we propose two improvements over previous methods with respect to dialogue slot-value constraint rules: (i) redefining the estimation conditions for the energy network; (ii) regularising label predictions following the dialogue slot-value constraint rules. In our results we find that our extended energy-based neural dialogue state tracker yields better overall performance in term of prediction accuracy, and also behaves more naturally with respect to the conversational rules.
Keywords: dialogue slot-value constraint rules; multi-label classification methods; real conversation scenarios; Dialogue processing; Multi-label classification; Label regularisation; F-measure optimisation; Energy-based learning; Neural dialogue state tracking